Pengujian Akurasi Data Potensi Kepuasan Pelanggan Kereta Commuterline (KRL) Dengan Algoritma C4.5 - al fiyan; Muhamad Fatchan; Irfan Afriantoro; Putri Anggun Sari; Endah Yaodah Kodratilah (DPPM Universitas Pelita Bangsa, 2021)
PT. KAI Commuter line (KRL) is a transportation service provider that was founded in 2008. There are many ways that transportation service companies can win the competition, including by increasing transportation customer satisfaction. This study aims to analyze the potential for KRL customer satisfaction by using data mining techniques with the C4.5 algorithm. The research instrument obtained data in the form of a questionnaire, the attributes of potential customer satisfaction in this study included price, facilities, services, and loyalty. This study uses 2 scales, namely the nominal scale in the form of codes or labels, and the interval scale in the form of weights in the answers to questions. In this study, the results obtained from several attributes produce a cause-and-effect relationship in classifying satisfied and dissatisfied customers. This research is hoped to be able to help the KRL party in increasing customer satisfaction to retain customers and increase the profit of the KRL company. The classification results using the C4.5 algorithm obtained an accuracy of 91.67%, which indicates that the C4.5 algorithm is suitable for measuring the potential for KRL customer satisfaction..